Contemporary studies on relationships, health, and wellness - Theiss, Jennifer; Greene, Kathryn (Advances in personal relationships (Cambridge, England), 2019)
"This volume showcases studies from various disciplines that are on the leading edge of research exploring the interdependence between health and relationships, including scholarship from the fields of communication, counseling, health services, human development and family studies, public health, and psychology. The research included in this volume highlights several relationship processes that are instrumental in the maintenance of health and the management of illness, including interpersonal influence, information management, uncertainty, social support, and communication. Although the existing health literature is rich with knowledge about individual and ecological factors that are influential in promoting certain health behaviors, relationship scholars have much to contribute in terms of documenting the interpersonal dynamics that are involved in experiences of health and illness"--Provided by publisher